Building of neomycin–nucleobase–amino acid conjugates for the inhibition of oncogenic miRNAs biogenesis. Issue 34 (17th August 2018) - Vo, Duc Duy; Becquart, Cécile; Tran, Thi Phuong Anh; Di Giorgio, Audrey; Darfeuille, Fabien; Staedel, Cathy; Duca, Maria
Abstract : Neomycin–nucleobase–amino acid conjugates bind to pre-miR-372 and inhibit Dicer-mediated processing thus leading to decreased levels of oncogenic miR-372 in vitro and in gastric adenocarcinoma cells. Abstract : MicroRNAs (miRNAs) are a recently discovered category of small RNA molecules that regulate gene expression at the post-transcriptional level. Accumulating evidence indicates that miRNAs are aberrantly expressed in a variety of human cancers, thus being oncogenic. The inhibition of oncogenic miRNAs (defined as the blocking of miRNAs' production or function) would find application in the therapy of different types of cancer in which these miRNAs are implicated. In this work, we describe the design and synthesis of new small-molecule RNA ligands with the aim of inhibiting Dicer-mediated processing of oncogenic miRNAs. One of the synthesized compound (4b ) composed of the aminoglycoside neomycin conjugated to an artificial nucleobase and to amino acid histidine is able to selectively decrease miR-372 levels in gastric adenocarcinoma (AGS) cells and to restore the expression of the target LATS2 protein. This activity led to the inhibition of proliferation of these cells. The study of the interactions of4b with pre-miR-372 allowed for the elucidation of the molecular mechanism of the conjugate, thus leading to new perspectives for the design of future inhibitors.